Color-Texture Image Analysis of Coral Reefs - Marcos, Ma. Sheila Angeli; Soriano, Maricor; Oblefias, Wilma; Quibilan, Miledel; Saloma, Caesar (Science Diliman: A Journal of Pure and Applied Sciences; Vol 13 No 2 (2001), 2012)
Excerpt Marine scientists assess the condition of coral reefs from estimates of the population of living corals, dead corals, algae, rocks, and other animals coexisting in the reefs. Some popular methods used for assessment are Line Intercept Transect (LITR) and In-Situ Mapping (ISMP) where both methods employ a diver that notes the population of benthic organisms in an area of a reef of interest though of different techniques of sampling. A rapid and consistent method employed since 1992 to estimate percentage cover of sessile reef organisms is the Video Recording (VIDR) (Uychiaoco et al., 1992). The area of interest is filmed and then processed by a method called Video Point Sampling (VIDS) (Carleton & Done, 1995). Expert individuals estimate the percent cover through random or fixed points placed on the monitor screen while the film is paused at random or even intervals and identifying the items underlying the sampling points on the appropriate benthos category (e.g. alive coral, dead coral, rock). A software called PointCount’99 (http://www.cofc.edu/~coral/pc99/Pcppintro.htm) also operates as that of the VIDS, using the random point count method and still requiring user-intervention to classify items at specified points. Assessment in the said methods is visual, requiring a trained eye and experience. By automating the assessment with a computer, the analysis is more precise, less subjective and less tedious.